Food safety knowledge, attitudes and practices of street food vendors and consumers in Port-au-Prince, Haiti. (April 2015) - Samapundo, S.; Climat, R.; Xhaferi, R.; Devlieghere, F.
Abstract: This study had the major objective of determining the food safety knowledge, attitudes and practices of vendors and consumers of street food in Port-au-Prince, Haiti. Haiti currently has no food safety legislation in place. 160 consumers and 80 vendors from four different communes (Tabarre, Delmas, Pétion-ville and downtown Port-au-Prince) volunteered to participate in the study. In general, consumers and vendors exhibited average food safety knowledge and attitude levels. Gender, training, level of education and location did not have a significant effect ( p < 0.05) on the level of food safety knowledge of the consumers. Vendors were determined to have higher levels of food safety knowledge than consumers, whilst trained vendors had better food safety knowledge and attitudes compared to untrained vendors. The majority of vendors and consumers were aware of the importance of washing hands and proper cleaning with regards to the prevention of foodborne diseases. However, some other aspects were of concern. Consumers and vendors did not know that Hepatitis A, Salmonella spp. and Staphylococcus spp. are pathogens responsible of foodborne diseases. They also had difficulties in identifying the groups at risk of foodborne diseases and most were unaware of the importance of reheating food to fight against foodborne diseases. In the observational part of the study, it was found that in 60% of the cases, flies and animals were evident around the stall and 65% did not have access to potable water. The majority served food with bare hands and did not wash their hands after handling money. Additionally, 70% of the vendors did not chill pre-cooked food. The conditions in which street food vendors operate in Port-au-Prince are largely unacceptable from a food safety point of view and an effort should be made to provide them with adequate infrastructure including potable water, toilets and waste disposal facilities. The results of this study should be used to generate part of the impetus towards the development of enforcement of appropriate food safety legislation in Haiti. Highlights: Food safety knowledge, attitudes, and practices were evaluated in Port-au-Prince. 160 consumers and 80 vendors from four different communes participated. Consumers and vendors exhibited average food safety knowledge and attitude levels. Vendors generally have higher levels of food safety knowledge than consumers. Street food vendors in Port-au-Prince operate under largely unhygienic conditions.